2015
DOI: 10.1021/am5075634
|View full text |Cite
|
Sign up to set email alerts
|

Interface Chemistry and Molecular Bonding of Functional Ethoxysilane-Based Self-Assembled Monolayers on Magnesium Surfaces

Abstract: The modification of magnesium implants with functional organic molecules is important for increasing the biological acceptance and for reducing the corrosion rate of the implant. In this work, we evaluated by a combined experimental and theoretical approach the adsorption strength and geometry of a functional self-assembled monolayer (SAM) of hydrolyzed (3-aminopropyl)triethoxysilane (APTES) molecules on a model magnesium implant surface. In time-of-flight secondary ion mass spectrometry (ToF-SIMS) and X-ray p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…HT leads to a slight increase in dye loading, which may be related to desorption of contaminants or induction of reactions between previously physisorbed species. 33 Results demonstrated that up to 65% more dye may be incorporated on the surface through the formation of phosphate−metal oxide bilayers on anatase. No adverse effects of the bilayers on the photoelectronic properties of anatase TiO 2 were observed by incident photon to current efficiency (IPCE) analysis 40 (see Figures S4 and S5).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…HT leads to a slight increase in dye loading, which may be related to desorption of contaminants or induction of reactions between previously physisorbed species. 33 Results demonstrated that up to 65% more dye may be incorporated on the surface through the formation of phosphate−metal oxide bilayers on anatase. No adverse effects of the bilayers on the photoelectronic properties of anatase TiO 2 were observed by incident photon to current efficiency (IPCE) analysis 40 (see Figures S4 and S5).…”
Section: Resultsmentioning
confidence: 97%
“…HT leads to a slight increase in dye loading, which may be related to desorption of contaminants or induction of reactions between previously physisorbed species . Results demonstrated that up to 65% more dye may be incorporated on the surface through the formation of phosphate–metal oxide bilayers on anatase.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations